Peningkatan Keterampilan Menyimak Dengan Media Pembelajaran Audio Visual Pada Siswa Kelas IV SD Inpres 33 Ambon: Indonesia - Marthinus, Martha; Ririhena, Ribka L.; Notanubun, Zainudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the improvement in listening skills using audio-visual learning media in fourth-grade students at SD Inpres 33 Ambon. The research method used in this study was Classroom Action Research (CAR). The results of the study showed that based on the initial test results, which were 59.46 or classified as adequate, there was an improvement in the results of the first cycle test to 65.21, also classified as adequate, and in the results of the second cycle test, the score obtained was 83.61, classified as good. This demonstrates an improvement from the initial test to Cycle II. This improvement indicates that listening comprehension learning using audio-visual learning media among fourth-grade students at SD Inpres 33 Ambon can be successfully implemented.